2011
DOI: 10.1016/j.jbiotec.2011.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing of the Chinese hamster ovary microRNA transcriptome: Identification, annotation and profiling of microRNAs as targets for cellular engineering

Abstract: Chinese hamster ovary (CHO) cells are the predominant cell factory for the production of recombinant therapeutic proteins. Nevertheless, the lack in publicly available sequence information is severely limiting advances in CHO cell biology, including the exploration of microRNAs (miRNA) as tools for CHO cell characterization and engineering. In an effort to identify and annotate both conserved and novel CHO miRNAs in the absence of a Chinese hamster genome, we deep-sequenced small RNA fractions of 6 biotechnolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 60 publications
(68 reference statements)
2
63
0
Order By: Relevance
“…Next‐generation sequencing (NGS) data were obtained by Illumina sequencing as described by Hackl et al (2011) and is available at the Sequence Read Archive SRA (www.ncbi.nlm.nih.gov/sra/), accession number SRA024456.1. Cell lines sequenced included CHO‐DUXB11 (ATCC CRL‐9096), CHO‐K1 (ECACC‐CCL‐61), and two derivative recombinant cell lines producing a monoclonal antibody (CHO‐K1) and an EpoFc fusion protein (DUXB11).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next‐generation sequencing (NGS) data were obtained by Illumina sequencing as described by Hackl et al (2011) and is available at the Sequence Read Archive SRA (www.ncbi.nlm.nih.gov/sra/), accession number SRA024456.1. Cell lines sequenced included CHO‐DUXB11 (ATCC CRL‐9096), CHO‐K1 (ECACC‐CCL‐61), and two derivative recombinant cell lines producing a monoclonal antibody (CHO‐K1) and an EpoFc fusion protein (DUXB11).…”
Section: Methodsmentioning
confidence: 99%
“…In 2011, the first systematic approaches to miRNA annotation in CHO cells were reported (Hackl et al, 2011; Johnson et al, 2011). Subsequent studies were focused on providing insights into the importance of miRNAs for molecular pathways relevant to cell culture engineering, such as growth (Jadhav et al, 2014), apoptosis (Druz et al, 2011), and protein secretion (Barron et al, 2011; Loh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA deep sequencing data of different CHO lines indicated that approximately 400 miRNAs are expressed in CHO cells. 48 Although Chinese hamsters possess a considerably lower number of chromosomes (n=22) compared to mice (n=40), the genomic information is highly overlapping. 49 Thus, the presence of only 400 different miRNAs appears to be underestimated and recently reported computational re-analysis of CHO genomic data identified hundreds of additional pre-miR sequences.…”
Section: Vast Numbers Of Mirnas Regulate Crucial Cellular Pathwaysmentioning
confidence: 99%
“…The repetitious sequences make de novo assembly of these genomes difficult without a reference genome and only slightly easier when a reference genome is available. A large variety of research pursuits is achievable and within the animal cell technology community, Illumina has been used to sequence the Chinese hamster (Brinkrolf et al 2013;Lewis et al 2013) and CHO Xu et al 2011) genomes, as well as baby hamster kidney and CHO cell line transcriptomes (Johnson et al 2014;Hackl et al 2011). Overall, the Illumina platform is able to produce large amounts of high-quality data via a low-cost, high-throughput methodology.…”
Section: Illuminamentioning
confidence: 99%